2018
DOI: 10.1111/ddi.12785
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the correlates of species and site contributions to beta diversity in dung beetle assemblages

Abstract: AimWe aimed to test whether contributions of individual species (SCBD) and contributions of single sites (LCBD) to overall beta diversity can be predicted by species metrics and species characteristics and also by community metrics and ecological variables, respectively.LocationA mainland‐island landscape in the southern Brazilian Atlantic Forest domain.MethodsDung beetles were sampled along 100 sampling units within four large forest fragments. We partitioned beta diversity into SCBD and LCBD aiming to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 50 publications
12
81
1
2
Order By: Relevance
“…Supporting this conclusion, positive relationships between species contributions to beta diversity and site occupancy have recently been documented in several studies (e.g. Gavioli, Milardi, Castaldelli, Fano, & Soininen, 2019;Heino & Grönroos, 2017;da Silva, Hernández, & Heino, 2018). Rapid recolonization of formerly dry habitat is likely to occur after the cessation of drought (Lennox, Crook, Moyle, Struthers, & Cooke, 2019).…”
Section: Discussionmentioning
confidence: 64%
“…Supporting this conclusion, positive relationships between species contributions to beta diversity and site occupancy have recently been documented in several studies (e.g. Gavioli, Milardi, Castaldelli, Fano, & Soininen, 2019;Heino & Grönroos, 2017;da Silva, Hernández, & Heino, 2018). Rapid recolonization of formerly dry habitat is likely to occur after the cessation of drought (Lennox, Crook, Moyle, Struthers, & Cooke, 2019).…”
Section: Discussionmentioning
confidence: 64%
“…Large LCBD values indicate high importance of the given province to the overall beta diversity. Recent applications of the LCBD approach are described by Tonkin et al (2016), Heino & Grönroos (2017), Vad et al (2017) and da Silva et al (2018).…”
Section: Response Variablesmentioning
confidence: 99%
“…Recently, Legendre and De Cáceres (2013) devised a method to decompose total beta diversity in the contributions of species or sites, where the relative ecological uniqueness of sites can be evaluated [i.e. Empirical research on the topic has thus far revealed that species richness is typically negatively correlated with LCBD across local ecological assemblages, although there is some variation around the relationship (Legendre & De Cáceres, 2013;, Vilmi et al, 2017, Landeiro et al, 2018, da Silva et al, 2018. Empirical research on the topic has thus far revealed that species richness is typically negatively correlated with LCBD across local ecological assemblages, although there is some variation around the relationship (Legendre & De Cáceres, 2013;, Vilmi et al, 2017, Landeiro et al, 2018, da Silva et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples exhibiting DNA swamping had higher Local Contributions to Beta Diversity (LCBD) than the rest (Table S10), a measure of the uniqueness of one sample compared to the rest of its group (Legendre and Caceres, 2013). LCBD has been increasingly valued for conservation applications where researchers recommend protecting sites with extreme low and high LCBD (da Silva et al, 2018). In the 18S results of eukaryotes, there were 20 sites with significant higher or lower LCBD compared to their neighbors, 7 of which met our criteria as swamped.…”
Section: Resultsmentioning
confidence: 99%